2008
DOI: 10.1111/j.1540-8159.2008.01204.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Implantable Cardioverter‐Defibrillator Recalls on Patients' Anxiety, Depression, and Quality of Life

Abstract: Background In the past 2 years, multiple implantable cardioverter defibrillator (ICD) manufacturers have issued recalls on ICD models due to the potential for serious malfunction and even patient death. Previous studies examining the relationship between these recalls and patients' psychological well-being have been limited by small sample size and conflicting results. The purpose of this study is to examine the association between ICD recalls and patients' anxiety, depression, and quality of life. Methods P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 38 publications
(57 reference statements)
1
30
0
3
Order By: Relevance
“…Most studies reported data on secondary prevention patients. Only 6 studies [22,23,[33][34][35][36] reported data by indication, but all had less than, or equal to, 20 patients in the primary or secondary groups, and none found significant primary versus secondary differences in symptoms of anxiety or depression (not shown).…”
Section: Primary Versus Secondary Indicationmentioning
confidence: 80%
“…Most studies reported data on secondary prevention patients. Only 6 studies [22,23,[33][34][35][36] reported data by indication, but all had less than, or equal to, 20 patients in the primary or secondary groups, and none found significant primary versus secondary differences in symptoms of anxiety or depression (not shown).…”
Section: Primary Versus Secondary Indicationmentioning
confidence: 80%
“…The impact of device recall has been assessed in 6 studies. Four studies found no difference in psychological response between those with and without a device recall, 71,[73][74][75] whereas 2 studies reported a heightened level of anxiety at the time of evaluation after a device recall. 72,75 Collectively, ICD recalls remain under study, but more recent data suggest that ICD patients can generally tolerate the specter of recall and appreciate receiving information from the physician or manufacturer 96 but have more significant distress if that recall results in an adverse event such as a shock.…”
Section: Device Events and Recallmentioning
confidence: 98%
“…Several studies showed that patients with CIEDs affected by advisories experienced higher levels of anxiety, ICD concerns, and distress than patients with CIEDs unaffected by advisories (10,12,14,15). In the other studies, device advisories had no adverse psychological impact on affected patients (9,11,13,16,17). …”
Section: Introductionmentioning
confidence: 76%